MANAGING AND OPTIMIZING INNOVATION PROCESSES IN COLLABORATIVE AND VALUE CREATING NETWORKS - ESCHENBAECHER, JENS; GRASER, FALK (International Journal of Innovation and Technology Management (IJITM), 2011)
Management and optimization of innovation processes are highly important for every company that depends on keeping up with market and technological evolution. Methods for the managing and optimizing of innovation processes in networks are just beginning to arise. Among different ways of creating value, successfully managed innovation processes bear the highest overall potential: On the operational level, it creates immediate value in terms of new products while on the strategic level, survival and competitiveness of the company can be assured by creating long-range, intangible values like technology leadership and a secured position in an ever-changing market environment. Therefore, innovation in networks has entered the spotlight of scientific research and industrial application. It requires new managing concepts and sophisticated information-technology-based tools. In this article, we present a model that allows to manage structural relationships within innovation networks and additionally to introduce a conceptual optimization approach.